Impression Management in The Letters to Shareholders of Listed Entities: A Romanian Case Study - Maria-Silvia Săndulescu; Cătălin-Nicolae Albu (Journal of Accounting and Management Information Systems (JAMIS), 2018)
There is recent increased interest in investigating the way corporate reports are used to convey management's view of organizational performance. While previous research was mainly conducted in developed economies, the case of emerging economies in Southeast Europe provides new insights as these countries are characterized by poorer corporate governance mechanisms, a lack of transparency and higher ownership concentration. We fill this gap in literature by investigating the letters to shareholders issued by OMV Petrom, the largest oil and gas producer in Southeast Europe. Using content analysis, we evaluate the tone used by managers in their disclosures in order to identify any reporting biases via impression management techniques. Even though OMV Petrom is perceived in literature as a benchmark for reporting transparency, our results provide evidence of promotional aspects used in corporate narratives.
Keywords: D82; M41; 650; impression management; content analysis; financial performance; tone; corporate narratives; emerging economies